Invisible but sensible aesthetic aspects of excellence in nursing - Herholdt-Lomholdt, Sine Maria (Nursing philosophy, 2019)
Based on a Lived Experience Description written by an experienced nurse in Denmark, this article offers an ontological and existential-phenomenological exploration of aesthetic dimensions of excellence in nursing. In the research of Patricia Benner and colleagues, excellence in nursing is described as a matter of intuitive pattern recognition based on clinical experience and narrative understanding. In this article, and based on phenomenological reflections and philosophical inspirations from the Danish philosopher Dorthe Jørgensen and the French philosopher Maurice Merleau-Ponty, I suggest an extended understanding of excellence in nursing, and I argue that the work and research of Benner seem to overlook ontological and aesthetic aspects of excellence in nursing. This article argues that aesthetic aspects of excellence in nursing can be comprehended as moments where nurses sense a surplus of meaning and moments where the nurse and the patient share and are subjected to communal and unfolding life phenomena. Aesthetic dimensions of being in nursing can, from an ontological approach, best be described as similar to the way human beings listen to a piece of music or to how artists try to give a voice to the world: as a resonant way of being and becoming within the moment.